Developing a Drill-and-Practice-Based Scratching Learning Media to Improve Mathematical Problem-Solving Skills and Students' Mathematics Learning Motivation Junior High School 2, Tebing Tinggi City - Utari, Kania; Rajagukguk, Waminton; Surya, Edy (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
Students should be able to answer real-life math problems; therefore, mathematical problem-solving is crucial. Math problem-solving is improved by computer media. Educational media that meets students' needs motivates and inspires them, enhancing learning outcomes. Students' quantitative problem-solving skills will improve math learning results. Scratch is a computer-based learning tool that improves learning. The goal of this research is to use Scratch as a learning medium to improve students' mathematical problem-solving skills and motivation to learn mathematics. SMP Negeri 2 Kota Tebing Tinggi 7th graders completed this investigation in 2024/2025. This development research produced a valid, practical, and successful drill-and-practice-based visual learning medium to improve students' problem-solving and learning motivation. Media validity averaged 3.40, material validity 3.60, and linguistic validity 3.79. Teacher questionnaire scores averaged 3.67, while student questionnaire scores averaged 3.13 in the "Interested" category. The average learning implementation score rose to 3.25 in the second trial. Improved mathematical problem-solving and motivation were "moderate."